Prisoner of Pinochet : my year in a Chilean concentration camp - Bitar, Sergio; Editores, Pehuen (Critical human rights., 2017)
September 11, 1973: Chilean military forces under General Augusto Pinochet overthrew the elected government of President Salvador Allende, bombing the presidential palace with the president inside. Minister of Mining Sergio Bitar was forcibly detained along with other members of the Allende cabinet and confined on bleak, frigid Dawson Island in the Magellan Straits. Prisoner of Pinochet is the gripping first-person chronicle of Bitar's year as a political prisoner before being expelled from Chile; a poignant narrative of men held captive together in a labor camp under harsh conditions, only able to guess at their eventual fate; and an insightful memoir of the momentous events of the early 1970s that led to seventeen years of bloody authoritarian rule in Chile. Available in English for the first time, this edition includes maps and photos from the 1970s and contextual notes by historian Peter Winn.